Use of recycled coal bottom ash in reinforced concrete beams as replacement for aggregate - Karalar, Memduh; Bilir, Turhan; Çavuşlu, Murat; Özkiliç, Yasin Onuralp; Sabri Sabri, Mohanad Muayad (Frontiers in Materials, 2022)
In this research, it is studied the crack and flexural behavior of reinforced concrete beams with various bottom ash ratios (BARs) considered as fine aggregate in an experimental and numerical investigation. For experimental purposes, different concrete series are considered varying aggregate sizes ranging from 0 to 25 mm. To supplement concrete, bottom ash is put to use in conjunction with material from 0-5 mm in size aggregate particles as replacement for fine aggregates with ratios of 25%, 50%, 75%, and 100%. Experiments were done to investigate the behavior of the beams and how flexural and fracture behaviors are represented. 75% BARs gave optimum results in terms of displacement capacity. Increasing BAR to 100% decrease deflection capacity of the beam. Also, ANSYS software is used to build 3D finite element models (FEMs) of beams to compare with experiment data. Experimental and 3D numerical tests show exceptionally tight flexural and fracture behaviors. Following this, a computer-generated structure is made by running SAP2000, and the strength of the beams is then utilised in an RC structural model. Every stage of the building's construction is thoroughly assessed utilizing multiple types of seismic testing, employing the SAP2000 program, with the resulting analysis providing significant findings on how the seismic force of 75% BAR affects horizontal displacement of each floor. The results showed that the weight of the structure dramatically decreases as the number of columns and RCBs are raised while also increasing the number of BARs. Moreover, the magnitude of earthquake and BAR have a significant effect on the horizontal displacement behavior of reinforced concrete structures. The strength of the concrete structure varies between close- and far-fault earthquakes, and for close-fault earthquakes, concrete strength is stronger than for far-fault earthquakes. This brings us to the second disadvantage of BAR which is the 75% strain produces a severe displacement of reinforced concrete structures.